A prospective study of prevalence of anti-microbial susceptibility of bacterial isolates in lower respiratory tract infections - Husaain, Ajaz; Sultana, Qursheed; Ansari, M. Abdur Rab (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Lower respiratory tract infections (LRTIs) is one of the most common causes of mortality and morbidity across all age groups. In recent years, antibiotic resistance is constantly increasing. Thus, there is a need to monitor the bacteriological profile of pathogenic organisms. The present study aims to identify bacterial pathogens and their antibiotic susceptibility pattern. Methods: A prospective, observational, single centered study was conducted at tertiary care hospital for a period of 1 year i.e. from March 2016 to March 2017. A total of 733 sputum samples were collected and analyzed in microbiology lab. The samples went subjected to microscopy testing, culture and antibiotic sensitivity using suitable bacteriological methods. Results: From 733 sputum samples, about 51.34% were males and 48.56% were females. Approximately 49.65% of total samples were growth positive. Klebsiella was found to be the predominant microorganism followed by Methicillin sensitive Staphylococcus aureus (MSSA) and streptococcus. The gram-negative bacteria showed highest sensitivity for piperacillin/tazobactam, imipenem and ciprofloxacin. The gram-positive bacteria were found to be more susceptible for vancomycin, teicoplanin and amikacin. Conclusions: LRTIs are contagious form of disease and can rapidly disseminate among community. The irrational use of antibiotics complicates the management due to the antibiotic resistance. Local trend of antibiotic susceptibility pattern should be known as it helps in increasing the appropriate use of the antibiotics, decreasing the mortality and morbidity and reduces the anti-microbial resistance.